2010
DOI: 10.1024/1010-0652/a000018
|View full text |Cite
|
Sign up to set email alerts
|

Der Einsatz von vorgegebenen und selbst generierten Bildern als Textverstehenshilfe beim Lernen aus einem naturwissenschaftlichen Sachtext

Abstract: In dieser Arbeit wurde einerseits im Sinne der Theorien des multimedialen Lernens der Nutzen von vorgegebenen Bildern sowie andererseits im Sinne der Modelle des selbstregulierten Lernens der Nutzen von selbst generierten Bildern als Textverstehenshilfe untersucht. Anhand eines 2 × 2-faktoriellen experimentellen Designs mit den Faktoren «Bildpräsentation» und «Bildgenerierung» wurden die Effekte beider Arten des Bildeinsatzes an Schülern der 9. Klasse auf das Verständnis eines Sachtextes mit chemischem Lerninh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
2
0
8
Order By: Relevance
“…Wittrock, /2010, ) provides an alternative potential account of the learning benefits associated with hand movements. Research on the generative drawing principle (Schwamborn, Thillmann, Leopold, Sumfleth, & Leutner, ; Schwamborn, Thillmann, Opfermann, & Leutner, ; for a review, see Leutner & Schmeck, ) has found students who are instructed to create drawings while reading instructional text enjoy better learning outcomes, particularly when students hand‐draw using paper and pencil materials (e.g. Alesandrini, ; Leopold & Leutner, ).…”
Section: Embodied Cognition and Hand Movementmentioning
confidence: 99%
“…Wittrock, /2010, ) provides an alternative potential account of the learning benefits associated with hand movements. Research on the generative drawing principle (Schwamborn, Thillmann, Leopold, Sumfleth, & Leutner, ; Schwamborn, Thillmann, Opfermann, & Leutner, ; for a review, see Leutner & Schmeck, ) has found students who are instructed to create drawings while reading instructional text enjoy better learning outcomes, particularly when students hand‐draw using paper and pencil materials (e.g. Alesandrini, ; Leopold & Leutner, ).…”
Section: Embodied Cognition and Hand Movementmentioning
confidence: 99%
“…Studies that compared the effects of text and corresponding pictures (presented in a separated format) to a control group that learned without pictures, demonstrate benefits for the text-picture conditions (Butcher 2006;Leopold et al 2013;Schwamborn et al 2010). As students in these studies benefitted from the text and corresponding pictures without being instructed to create referential connections, students must have processed not only the text but also the pictures.…”
Section: Introductionmentioning
confidence: 99%
“…Auf der anderen Seite besteht die Möglichkeit seitens der Lehrperson, den Schwierigkeitsgrad eines Textes zu reduzieren (z.B. Klingner, 2015;Leisen, 2007;Schwamborn et al, 2010). Leisen (2007) differenziert zwischen einer offensiven Anpassung des Lesers an den Text und einer defensiven Anpassung des Textes an die lesende Person (siehe Abbildung 2.2).…”
Section: Lernunterstützung Durch Text-bild-kombinationenunclassified
“…E. Mayer & Moreno, 2003) bezeichnet und ist Gegenstand der Forschung multimedialer Lernumgebungen (z.B. R. E. Mayer, 2012Mayer, , 2022Paivio, 1986;Schnotz, 2014;Schnotz & Bannert, 2003;Schwamborn et al, 2010). Wichtige theoretische Grundlagen bezüglich des Multimedia Effekts liefern die Cognitive Load Theory (Sweller, 1988(Sweller, , 1994(Sweller, , 2010(Sweller, , 2012Sweller et al, 2011;Sweller et al, 2019), die duale Kodierungstheorie (Paivio, 1986), die Cognitive Theory of Multimedia Learning (R. E. Mayer, 2012Mayer, , 2022R.…”
Section: Lernunterstützung Durch Text-bild-kombinationenunclassified
See 1 more Smart Citation